2002
DOI: 10.1186/1475-2867-2-16
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of DNA damage and mitochondrial injury caused by hydrogen peroxide in SV-40 transformed lung epithelial cells

Abstract: BackgroundSince lung epithelial cells are constantly being exposed to reactive oxygen intermediates (ROIs), the alveolar surface is a major site of oxidative stress, and each cell type may respond differently to oxidative stress. We compared the extent of oxidative DNA damage with that of mitochondrial injury in lung epithelial cells at the single cell level.ResultDNA damage and mitochondrial injury were measured after oxidative stress in the SV-40 transformed lung epithelial cell line challenged with hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Mitochondrial activity was stimulated by H 2 O 2 alone and in combination with NO 2− at the nspDBD conditions in comparison to the untreated control, as shown inFigure 6b,e. H 2 O 2 is a potent oxidizer and is well known to induce mitochondrial stress at concentrations as low as 100 µM[50]. NO 2 − alone had no discernable effect on mitochondrial O 2 − production for either of the mock treatments.…”
mentioning
confidence: 95%
“…Mitochondrial activity was stimulated by H 2 O 2 alone and in combination with NO 2− at the nspDBD conditions in comparison to the untreated control, as shown inFigure 6b,e. H 2 O 2 is a potent oxidizer and is well known to induce mitochondrial stress at concentrations as low as 100 µM[50]. NO 2 − alone had no discernable effect on mitochondrial O 2 − production for either of the mock treatments.…”
mentioning
confidence: 95%
“…It is possible that C6 glioma cells have inherent protection mechanisms from ROS-induced DNA damage aside from neutralizing ROS such as enhanced DNA repair processes. Previous studies in alveolar epithelium have demonstrated resistance to DNA damage in spite of chronically elevated H 2 O 2 concentrations 52 . Further studies are warranted on the unique nature of C6 cells to further understand their resistance to pFUS-induced DNA damage.…”
Section: Discussionmentioning
confidence: 96%